Toward Synergies of Ketamine and Psychotherapy - Mathai, David S.; Mora, Victoria; Garcia-Romeu, Albert (Frontiers in Psychology, 2022)
Ketamine is a dissociative drug that has been used medically since the 1970s primarily as an anesthetic agent but also for various psychiatric applications. Anecdotal reports and clinical research suggest substantial potential for ketamine as a treatment in conjunction with psychological interventions. Here, we review historical and modern approaches to the use of ketamine with psychotherapy, discuss the clinical relevance of ketamine’s acute psychoactive effects, propose a unique model for using esketamine (one isomeric form of ketamine) with Acceptance and Commitment Therapy (ACT), and suggest considerations for moving medication-assisted psychotherapy forward as a field.